Early Freezing of Gait: Atypical versus Typical Parkinson Disorders. (15th February 2015) - Lieberman, Abraham; Deep, Aman; Dhall, Rohit; Tran, An; Liu, Ming-Jai
Abstract : In 18 months, 850 patients were referred to Muhammad Ali Parkinson Center (MAPC). Among them, 810 patients had typical Parkinson disease (PD) and 212 had PD for ≤5 years. Among the 212 patients with early PD, 27 (12.7%) had freezing of gait (FOG). Forty of the 850 had atypical parkinsonism. Among these 40 patients, all of whom had symptoms for ≤5 years, 12 (30.0%) had FOG. FOG improved with levodopa in 21/27 patients with typical PD but did not improve in the 12 patients with atypical parkinsonism. FOG was associated with falls in both groups of patients. We believe that FOG unresponsive to levodopa in typical PD resembles FOG in atypical parkinsonism. We thus compared the 6 typical PD patients with FOG unresponsive to levodopa plus the 12 patients with atypical parkinsonism with the 21 patients with typical PD responsive to levodopa. We compared them by tests of locomotion and postural stability. Among the patients with FOG unresponsive to levodopa, postural stability was more impaired than locomotion. This finding leads us to believe that, in these patients, postural stability, not locomotion, is the principal problem underlying FOG.